Prediction of the Risk of Myocardial Infarction from Polymorphisms in Candidate Genes - Yamada, Yoshiji; Izawa, Hideo; Ichihara, Sahoko; Takatsu, Fumimaro; Ishihara, Hitoshi; Hirayama, Haruo; Sone, Takahito; Tanaka, Masashi; Yokota, Mitsuhiro (The New England journal of medicine, 2002)
The risk of myocardial infarction is known to be influenced by genetic factors, but few such factors have been identified. This study found that a polymorphism in the connexin 37 gene in men and polymorphisms in the plasminogen-activator inhibitor type 1 gene and the stromelysin-1 gene in women were associated with an increased risk of myocardial infarction. The risk in men was influenced by a polymorphism in the connexin 37 gene. Myocardial infarction is a complex multifactorial and polygenic disorder that is thought to result from an interaction between a person's genetic makeup and various environmental factors. 1 , 2 In general, the incidence of myocardial infarction increases additively as a function of the number of conventional risk factors, including hypertension, diabetes mellitus, and hypercholesterolemia. 2 Although each risk factor itself is partly under genetic control, a family history of myocardial infarction is also an independent predictor, suggesting the existence of additional susceptibility genes for this condition. 1 Furthermore, some patients who have had a myocardial infarction do not have any conventional risk factors, suggesting . . .